Sociodemographic and pharmacoepidemiological profile of people on antiretroviral therapy in the coast of the state of Paraná - Marlon Silva; Frederico Alves Dias; Caroline Fournier Testoni; Doroteia Aparecida Höfelmann; Yanna Dantas Rattmann (Universidade Estadual de Maringá, 2022)
The aim of this study was to investigate possible factors related to antiretroviral therapy (ART) that contribute to the understanding of the highest rate of Aids detection on the coast of the state of Paraná, a port region identified administratively as the 1st Regional Health Division (1st HD) in the state of Paraná. Data on the sociodemographic profile of the population undergoing antiretroviral treatment (ART), medication changes, dropout of therapy, proportion of the population undergoing treatment and viral load were obtained through computerized systems. Between July 1, 2018 and June 31, 2019, 1,393 people were on ART in the 1st RS. Of these, 57.6% were male. During this period, 110 people started ART with a predominance of the age group between 30 and 39 years old. ART was switched for 169 people and 211 patient dropouts were detected. The proportion of people diagnosed with HIV without treatment (gap) is still high, however 92.7% people on ART have suppressed viral load. It can be concluded that the lower educational level of the population undergoing treatment, the late diagnosis of those infected and the treatment gap probably contribute to the highest rate of Aids detection in the 1st RS.